A língua e a história em documentos produzidos por Cruz e Souza no final do século XIX - Muramatsu, Maria de Lourdes Martins (2007)
In this Dissertation, while bringing Language and History closer to the social reality with the objective to check the references to the afro-american man and the abolition of slavery during the 19th century, it turned in the identification of some of the characteristics of the Portuguese in use to that time. While taking the language like social practice, we question in which measure the linguistic choices express the political, historical and intellectual positions of those days. The movement for the abolition of the slavery mobilized some of our intellectuals and the press that, allying with them, materialized occurred facts into documents, making them more understandable to the society. The recognition of the importance of the historical-linguistic context and of the analysis of the document does so that the man can reconstitute his own past and the past of the language, doing so they understand better this past by the light of the modern theories. The choice of the Linguistic Historiography as a theoretical and methodological support, is justified in virtue of the interdisciplinary apparatus that it established, in essence between Linguistics and the History, in the process of interpreting documents, comprising a spacious vision of the language and of the man, treating them in their totality and not only by the sociological or anthropological point of view, but in a linguistic dimension, fact that allows us to understand the man and his interaction with the social group. The resource of the metalanguage and the application of the principles proposed by Konrad Koerner are privileged in our analysis. We value the documentary character of the Piparotes texts produced by Cruz e Sousa for O Moleque newspaper between 1885, and which were taken like sample, coming to think that such texts were significant in the society of the time and helped rebuilding reality linguistically